The Other Side of 2020: Questioning Everything-Doing Something - Adam Tyma (Central States Communication Association, 2021)
In February of 2020, everything around the world changed. By mid-March, the majority of the world was locked down. Teachers were called on to create a sense of "normalcy" for their students. And we tried. During that process, though, as a teacher, I started to truly question what I was teaching and-more importantly-HOW I was teaching. This reflective essay offers a critical interrogation of my own pedagogical choices during and because of the COVID-19 pandemic . . . and so many other "moments" that have led up to it. I contend that we need to look in the mirror and ask ourselves, "Are we doing this right?" The following offers my starting point.